What do we know about the future of urbanization in relation to food systems? - Dorosh, Paul A.; Thurlow, James (International Food Policy Research Institute, 2025)
The world is urbanizing rapidly. The global urban population increased from 2.87 billion in 2000 to 4.38 billion in 2020, a 53 percent rise, and is projected to reach 6.57 billion by 2050, representing 68 percent of the world’s population (World Bank 2024a).